Microbial composition play the leading role in volatile fatty acid production in the fermentation of different scale of corn stover with rumen fluid - Zhang, Haiyan; Zhang, Wanqin; Wang, Shunli; Zhu, Zhiping; Dong, Hongmin (Frontiers in Bioengineering and Biotechnology, 2024)
Rumen fluid is a natural and green biocatalyst that can efficiently degrade biomass into volatile fatty acid (VFA) used to produce value-added materials. But the essence of high degradation efficiency in the rumen has not been fully analyzed. This study investigated the contribution of substrate structure and microbial composition to volatile fatty acid production in the fermentation of corn stover. The ball milled corn stover were innovatively applied to ferment with the rumen fluid collected at different digestion times. Exogeneous cellulase was also added to the ruminal fermentation to further reveal the inner mechanism. With prolonged digestion time, the microbial community relative abundance levels of Bacteroidetes and Firmicutes increased from 29.98% to 72.74% and decreased from 51.76% to 22.11%, respectively. The highest VFA production of the corn stover was achieved via treatment with the rumen fluid collected at 24 h which was up to 9508 mg/L. The ball milled corn stover achieved high VFA production because of the more accessible substrate structure. The application of exogenous cellulase has no significant influence to the ruminal fermentation. The microbial community abundance contributed more to the VFA production compared with the substrate structures.